The Effect of Bedding Structure on Mechanical Property of Coal - Zetian Zhang; Ru Zhang; Guo Li; Hegui Li; Jianfeng Liu (Advances in Materials Science and Engineering)
The mechanical property of coal, influencing mining activity considerably, is significantly determined by the natural fracture distributed within coal mass. In order to study the effecting mechanism of bedding structure on mechanical property of coal, a series of uniaxial compression tests and mesoscopic tests have been conducted. The experimental results show that the distribution characteristic of calcite particles, which significantly influences the growth of cracks and the macroscopic mechanical properties of coal, is obviously affected by the bedding structure. Specifically, the uniaxial compression strength of coal sample is mainly controlled by bedding structure, and the average peak stress of specimens with axes perpendicular to the bedding planes is 20.00 MPa, which is 2.88 times the average amount of parallel ones. The test results also show a close relationship between the bedding structure and the whole deformation process under uniaxial loading.